Identification of three strains of a virus associated with cassava plants affected by Frogskin disease - Calvert, Lee A.; Cuervo Ibáñez, Maritza; Lozano Potes, Iván; Villareal, N.; Arroyave, José A. (Wiley, 2008)
Cassava Frogskin Disease (CFSD) can cause severe damage to cassava roots and is one of the most important diseases of cassava in Latin America. The principal objective of this study was to identify the causal agent of CFSD. Electron microscopy, viral purifications, double-stranded RNA (dsRNA) analysis, cloning, sequencing, rtPCR and hybridizations were carried out to characterize and associate a novel virus with the disease. Virus-like particles of 70 and 45 nm in diameter were found in affected cassava plants and partially purified preparations respectively. Nine species of dsRNA were associated with this disease and cDNA clones to six genomic segments were synthesized from the purified dsRNAs. The putative proteins predicted from the sequence of the cassava virus cDNA clones have similarity with the P1, P2, P3, P4, P5 and P10 proteins of Rice ragged stunt virus (RRSV). Phylogenic analysis confirmed that this virus is a member of the family Reoviridae and is most closed related to RRSV. Hybridization analyses of dsRNA identified S1, S2, S3, S4, S5 and S10 genomic segments in the CFSD-affected plants, but not in healthy controls. Additionally, 26 isolates were compared using a portion of the putative polymerase gene. The virus was detected in all 26 isolates, and they were classified into three distinct races. The association of this virus with CFSD was strengthened by the detection of this virus in diseased plants collected from different locations throughout Colombia.